Prediction of Metallurgical Coke Strength from the Petrographic Composition of Coal Blends - Sutcu, H.; Toroglu, I.; Piskin, S. (TAYLOR & FRANCIS INC, 2009)
Turkey, especially Zonguldak on the West Coast of Black Sea region, has large reserves of bituminous coal that can be used either directly or in blends with other coals for metallurgical coke production. It is possible to predict the coking properties of these coals by petrographic analysis. In this study, semi- and non-coking coals were blended with coking bituminous coals in varying proportions and an estimation was made as to their stability factors through petrographic techniques. It was established that semi- and non-coking bituminous coals could be used in the production of metallurgical coke.
Keywords: bituminous coal; coke stability; metallurgical coke; petrography; Energy & Fuels; Engineering; Environmental Sciences & Ecology